Estudio de desórdenes músculo-esqueléticos y su incidencia en la salud laboral de los trabajadores de bodega de producto terminado de la empresa cervecera nacional s.a. planta cumbayá. Propuesta de un sistema ergonómico a implementarse en la empresa. - García Álava, Nexi Viviana (2017)
The musculoskeletal disorders are the most common group of diseases among occupational diseases declared (75%) of every 3 dollars in compensation, one engages in musculoskeletal disorders. The annual total is 15 to US $ 18 billion quadrupling this value if indirect costs are accounted for. In the EU has a cost of 2% of GDP. The overall objective was to study musculoskeletal disorders and occupational health of workers finished product warehouse company Cervecera Nacional S.A. Cumbayá plant. Based on the methods applied (OWAS, OCRA, Questionnaire Nordic Standardized and Test of Navarra) were diagnosed as: the effects caused by the postures are extremely harmful to the musculoskeletal system, involving a High Risk of occupational diseases requires measures immediate corrective, improving job, medical supervision and training; sintomatologías in the neck, lower back and ankles / feet are the highest incidence. According to the test of Navarra, most study subjects report that the area of Participation, Involvement, Responsibility has been: Unsuitable. (fifty%). The trend towards worse Very Inadequate in the area: Education, Information, Communication (55%). Area Time management has been Very Inadequate, by 50%. In the area: Cohesion Group status is inadequate (38%). 3. The information is systematized in the design of an ergonomic system for reducing Musculoskeletal Disorders in BPT staff of the company.